Improving Mathematics Learning Outcomes through the Teams Games Tournament (TGT) Cooperative Learning Model among Fourth-Grade Students - Muhammad Safar; Sulton Akbar; Lenita Rahmawati; Chofa Syalsa Bela; Agung Setyawan (Yayasan Citra Dharma Cindekia, 2026)
Mathematics learning outcomes of fourth-grade students at SDN Socah 3 were relatively low, particularly in plane geometry topic. This research aims to improve students' mathematics learning outcomes through the application of the Teams Games Tournamet (TGT) cooperative learning model. This classroom action research involved 24 fourth-grade students and was conducted in two cycles where each cycle consisted of planning, action, observation, and reflection stages. Data was collected using tests, observations, and documentation. The results of the study showed a consistent improvement in student learning outcomes. The average score increased from 48.54 in the pre-cycle stage with a completion percentage of 20.83%, to 62.58 with a completion rate of 54.17% in Cycle I, and then increased to 81.38 with a completion rate of 91.67% in Cycle II. These findings show that the TGT cooperative learning model can not only improve mathematics learning outcomes, but can also increase student engagement and participation during the learning process. Therefore, the TGT-type cooperative learning model can be considered an effective and contextual learning alternative to mathematics teaching in primary schools.